2004
DOI: 10.1023/b:gene.0000017639.62427.8b
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Morphological Traits Among Drosophila Melanogaster and D. Simulans: Genetic Variability, Clines and Phenotypic Plasticity

Abstract: The two sibling cosmopolitan species, Drosophila melanogaster and D. simulans, are able to proliferate under very different climatic conditions. This has resulted in local adaptations, which are often arranged in latitudinal clines. Such clines are documented for body weight, wing and thorax length, sternopleural and abdominal bristle number, ovariole number and thoracic pigmentation. The overall magnitude of geographical differentiation is, however, much less in D. simulans than in D. melanogaster, and latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 43 publications
11
67
2
3
Order By: Relevance
“…Reinforcing the arguments presented above, a higher predictability of the biology and dynamics of D. simulans, compared with Z. indianus, has been reported in worldwide studies (e.g. Karan et al 2000;Gibert et al 2004;David et al 2006;Yassin et al 2009;Commar et al 2012;van Heerwaarden et al 2012).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Reinforcing the arguments presented above, a higher predictability of the biology and dynamics of D. simulans, compared with Z. indianus, has been reported in worldwide studies (e.g. Karan et al 2000;Gibert et al 2004;David et al 2006;Yassin et al 2009;Commar et al 2012;van Heerwaarden et al 2012).…”
Section: Discussionsupporting
confidence: 74%
“…We made an additional change to the model for Z. indianus: we changed the cause-effect positive relationship mean temperature tem ? body size siz to the covariance relation tem $ siz because previous studies have demonstrated an inverse relationship for these variables (Nunney and Cheung 1997;Gibert et al 2004). The goodness of fit of the model was unchanged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Latitudinal clines in phenotypic traits within and among insect species are widespread (Nylin et al 1989;Gilchrist and Partridge 1999;Fox et al 2004;Gibert et al 2004). Because critical physiological processes in insects are thermally regulated (Taylor 1981), temperature is considered a major environmental factor influencing variability in morphological and life history traits along clines.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of laboratory populations have revealed that an intraspecific maximum ovariole number is attained with optimal larval nutrition at intermediate temperatures (Delpuech et al 1995;Thomas-Orillard 1984). In studies of natural populations of D. melanogaster and D. simulans, the ovariole number has been found to vary along a latitudinal cline, distinguishing populations within each species (Gibert et al 2004). Both species show a similar clinal variation in the ovariole number, establishing that different species respond in similar ways to environmental influences.…”
Section: Counting During Ovarian Morphogenesismentioning
confidence: 99%